Efficacy of a locally prepared live clone vaccine against Newcastle disease virus genotype IV and genotype VIId in Egypt: clone 30 vaccine - Abdelsabour, Mohammed A.; Helal, Ahmed M.; El Nagar, Eman M.S.; Walaa Abd El-fatah; Samah El Sayed Ali Abodalal; Madbouly, Yahia M.; Arafa, Abdelsatar A.; Ibrahim, Hazem M.; Hussein, Amel (Journal of Advanced Veterinary Research, 2024)
Vaccines against the virulent Newcastle disease virus (NDV) are broadly existing and can provide protection; nevertheless, better immunization practices are required to avoid clinical disease and limit virus circulation. This study evaluating the immunogenicity and protective efficiency of locally prepared clone 30 live-attenuated vaccine against the challenge impact of virulent NDV genotype IV and genotype VIId prevalent in Egypt in comparison with the commercially prepared live Lasota vaccine as a positive control group. The efficacy of the vaccine was evaluated based on the antibody titer, protection rate, oropharyngeal, and cloacal shedding. Therefore, 150 one day old specific pathogen free chicks (SPF) were divided in to three groups 50 bird per group (G).G1and G2 received 100 Âµl containing 6 log 10 EID50 via the oculo-nasal route of clone 30 vaccine and lasota vaccine in order, while G3 (un vaccinated) received sterile saline at the same route and dose. On day 21 post vaccination (pv) 40 bird from each group were challenged with a dose of 6.5 log10/ml EID50 intramuscular per bird for both genotype IV and genotype VIId (20 bird /genotype virus),the other 10 birds left from each group were kept separate for antibody level monitoring for the 6th week pv. Results revealed that, during vaccine preparation, the clone 30 virus showed a high virus titer when propagated in SPF embryonating chicken eggs (SPF-ECEs), which reached 1012/EID50/ml. The protection rate due to the clone 30 vaccine and the lasota vaccine was alike and showed 75% and 70% against challenge with genotype IV and genotype VIId, respectively, there were no significant differences (p > 0.05) between the antibody titer produced by the clone 30 vaccinated group and lasota group. Both the clone 30 and lasota vaccines showed nearly similar levels of oropharyngeal and cloacal shedding. The results clarify that, although there were no detected differences between the immune response and the protective efficacy of clone 30 vaccine and lasota vaccine but, the use of clone 30 vaccine is still advantageous for its superior immunogenicity and low post-vaccinal reaction, which will make the clone 30 vaccine suggestive for primary immunization, especially in immunologically naive birds. In conclusion, the prepared Clone 30 vaccine in the current study is safe for chicks and can be used as an effective vaccine against the circulating NDV.